Analysis and Research on the Temperature and Thermal Change of NC Machine Tool Electric Spindle Based on ANSYS Software. Issue 3 (October 2020) - Wu, Weimin
Abstract: With the improvement of CNC technology, CNC machine tools are gradually moving towards high speed, high precision and multi-function. Due to the comprehensive effect of internal and external heat sources, the thermal deformation of the motorized spindle has become the main factor affecting the machining accuracy of the machine tool in high-speed machining. ANSYS software is a large-scale general-purpose finite element analysis software integrating structure, fluid, electric field, magnetic field, and sound field analysis. It can interface with most CAD software, realize data sharing and exchange, and can effectively analyze the temperature and thermal changes of CNC machine tools. Therefore, this paper analyses the thermal deformation mechanism of the spindle of CNC machine tools in computer software, to provide the basis for reducing the thermal deformation of the motorized spindle of CNC machine tools in the future.